Clinical and genetic findings in two siblings with X-Linked agammaglobulinemia and bronchiolitis obliterans: a case report - Ronaldo da Silva Francisco Junior; Guilherme Loss de Morais; Joseane Biso de Carvalho; Cristina dos Santos Ferreira; Alexandra Lehmkuhl Gerber; Ana Paula de C Guimarães; Flávia Anisio Amendola; Fernanda Pinto-Mariz; Zilton Farias Meira de Vasconcelos; Ekaterini Simões Goudouris; Ana Tereza Ribeiro de Vasconcelos (BMC, 2022)
Abstract Background X-linked agammaglobulinemia (XLA) is an Inborn Errors of Immunity (IEI) characterized by pan-hypogammaglobulinemia and low numbers of B lymphocytes due to mutations in BTK gene. Usually, XLA patients are not susceptible to respiratory tract infections by viruses and do not present interstitial lung disease (ILD) such as bronchiolitis obliterans (BO) as a consequence of acute or chronic bacterial infections of the respiratory tract. Although many pathogenic variants have already been described in XLA, the heterogeneous clinical presentations in affected patients suggest a more complex genetic landscape underlying this disorder. Case presentation We report two pediatric cases from male siblings with X-Linked Agammaglobulinemia and bronchiolitis obliterans, a phenotype not often observed in XLA phenotype. The whole-exome sequencing (WES) analysis showed a rare hemizygous missense variant NM_000061.2(BTK):c.1751G>A(p.Gly584Glu) in BTK gene of both patients. We also identified a gain-of-function mutation in TGFβ1 (rs1800471) previously associated with transforming growth factor-beta1 production, fibrotic lung disease, and graft fibrosis after lung transplantation. TGFβ1 plays a key role in the regulation of immune processes and inflammatory response associated with pulmonary impairment. Conclusions Our report illustrates a possible role for WES in patients with known inborn errors of immunity, but uncommon clinical presentations, providing a personalized understanding of genetic basis, with possible implications in the identification of potential treatments, and prognosis for patients and their families.